Rheological study of chitosan and its blends: An overview - El-hefian, E.A.; Yahaya, A.H. (2010)
Chitosan, a modified natural carbohydrate polymer derived from carapaces of crabs and shrimps, has received a great deal of attention for its applications in diverse fields owing to its biodegradability, biocompatibility, non-toxicity and anti-bacterial property. The wide-ranging applications involve a broad spectrum of characterisation techniques and rheology represents one technique of growing importance in this field. This paper is an attempt to review the latest development in the rheology of chitosan, either on its own or associated with other materials, including the parameters that strongly influence its rheological behaviour such as concentration, pH and temperature.